2008
DOI: 10.1017/s1473550408004187
|View full text |Cite
|
Sign up to set email alerts
|

Jupiter – friend or foe? I: The asteroids

Abstract: : The asteroids are a major source of potential impactors on the Earth today. It has long been assumed that the giant planet Jupiter acts as a shield, significantly lowering the impact rate on the Earth from both cometary and asteroidal bodies. Such shielding, it is claimed, enabled the development and evolution of life in a collisional environment, which is not overly hostile. The reduced frequency of impacts, and of related mass extinctions, would have allowed life the time to thrive, where it would otherwis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 17 publications
3
68
0
Order By: Relevance
“…We note a great deal of similarity between this method of calculating average impact probabilities and the technique of simulating actual impact probabilities from orbit integrations by "super-sizing" the terrestrial planets (Horner & Jones 2008;Horner et al 2009). The idea is the same, and these authors noted that no unforeseen drawbacks had been found in detailed tests.…”
Section: The Hill Sphere Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note a great deal of similarity between this method of calculating average impact probabilities and the technique of simulating actual impact probabilities from orbit integrations by "super-sizing" the terrestrial planets (Horner & Jones 2008;Horner et al 2009). The idea is the same, and these authors noted that no unforeseen drawbacks had been found in detailed tests.…”
Section: The Hill Sphere Methodsmentioning
confidence: 99%
“…Thus, like the abovementioned super-sizing technique (Horner & Jones 2008), it has to be used with care, even though it works well in almost all situations. Returning now to Fig.…”
Section: Checks Of Consistency Between the Methodsmentioning
confidence: 99%
“…Horneck et al 2016); (ii) the formation and maintenance of an atmosphere that enables the presence of liquid water (Grenfell et al 2010); (iii) the existence of a magnetic field that could protect the surface from high-energy particles (Lundin et al 2007); (iv) climate stabilization, possibly via the presence of a large moon (Laskar et al 1993); (v) environmental diversity and climate-stabilizing feedbacks, for example due to the presence of plate tectonics which favours the carbonate-silicate cycle (e.g. Korenaga 2011;Höning & Spohn 2016); (vi) planetary protection from impacts due to the presence of gas giants (Horner & Jones 2008); and (vii) the properties of the central star (Beech 2011). It should be noted that complex molecules such as proteins have a limited range of temperature over which they are stable.…”
Section: Habitabilitymentioning
confidence: 99%
“…The bulk of that structure is the direct result of perturbations from Jupiter, and, to a lesser extent, Saturn. Jupiter also acts to control the flux of small bodies to the inner solar system, acting to perturb asteroids and comets onto Earth-crossing orbits (e.g., Laakso et al 2006;Horner & Jones 2008. Jupiter also hosts a large population of Trojan asteroids (Fornasier et al 2007;Vinogradova & Chernetenko 2015) and irregular satellites, both of which are thought to have been captured during the giant planet's migration (e.g., Sheppard & Jewitt 2003;Morbidelli et al 2005;Jewitt & Haghighipour 2007;Lykawka & Horner 2010).…”
Section: Introductionmentioning
confidence: 99%